Influence of the granite screenings to the properties of the concrete paving blocks - Mindaugas Laurinavičius; Mindaugas Daukšys; Albertas Klovas (Engineering Structures and Technologies, 2012)
The research deals with the granite screenings as fine aggregate influence on the technological properties of concrete mixtures and on the physical and mechanical properties and durability of concrete paving. The following several compositions of concrete mixture for the production of environment arrangements are researched: fine aggregate using only 0/2 fraction sand (B1), 10% of 0/2 fraction sand replacing with 0/2 fraction granite screenings (B2) and using only granite screenings (B3). Concrete mixtures were prepared in the laboratory, and concrete paving blocks – in the factory. The technological properties of concrete mixtures and physical and mechanical properties of concrete paving blocks (made from the mentioned concrete mixtures) were determined; the durability of the products in the cycles of frost resistance was forecasted. The research results reveal that due to the properly selected ratio between sand and granite screenings in the fine aggregate, the characteristics of concrete paving blocks are better than using only sand as fine aggregate.